ANALISIS FAKTOR PENYEBAB STRES TENAGA KESEHATAN DI MASA PANDEMI COVID-19: NARATIVE REVIEW - Katarina Sembiring; Subhannur Rahman; Rian Tasalim (Universitas Muhammadiyah Banjarmasin, 2022)
The Covid-19 outbreak has plagued the entire world, so the WHO has included this outbreak in the category of a pandemic. In Indonesia, the data on cases of positive Covid-19 patients on March 2, 2020 were 4,239,396 people. Losses caused by the pandemic such as physical and mental disorders. This disruption is not only for patients diagnosed as positive for Covid-19, health workers are also threatened with their physical and mental health. The purpose of this study was to analyze the factors that cause stress in health workers during the Covid-19 pandemic: Narrative Review. The database used is Google Scholar. In this literature search using keywords in the form of: